Distributed feedback multipeak laser emission in Rhodamine 6G doped organic-inorganic hybrids - Oliveira, D. C.; Messaddeq, Younes [UNESP]; Dahmouche, K.; Ribeiro, Sidney José Lima [UNESP]; Goncalves, R. R.; Vesperini, A.; Gindre, D.; Nunzi, J. -M. (Springer, 2006)
Organic-inorganic hybrid materials were prepared from an ureasil precursor (ureapropyltriethoxysilane designated as UPTES) and acrylic acid modified zirconium (IV) n-propoxide. Thin films containing rhodamine 6G (Rh6G) were prepared by spin-coating on glass substrates with different Zr:Si molar ratios (Zr:Si = 75:25, 50:50 and 25:75). Refractive index, thickness, number of propagating modes and attenuation coefficient were measured at 543.5, 632.8 and 1550 nm wavelengths by the prism coupling technique. Distributed feedback (DFB) laser effect was observed and studied as a function of films thickness and refractive index.
Keywords: organic-inorganic hybrids; DFB lasers; waveguides